Non-Linearities of Complicated Lever Mechanisms of Electric and Hydraulic Drives - A. G. Strizhnev; A. N. Rusakovich (Наука и техника)
The paper determines conversion coefficients for mechanical transmissions of electric and hydraulic drives which are used in special equipment. Nonlinearities of conversion coefficients  for mechanical transmissions have been revealed in the paper. Standardized conversion coefficient has been proposed for compensation of mechanical transmission influence on operation of electric and hydraulic drives. The paper contains recommendations on the application of the obtained results.